Technology Integration Challenges in Elementary School Social Studies Education: A Systematic Literature Review - Unga Utari; Unga Utami (Madako Elementary School, 2026)
The rapid development of digital technology has changed learning practices in elementary schools, including social studies learning. However, the integration of technology in social studies learning in elementary schools still faces various challenges that affect learning effectiveness and student engagement. This study aims to identify and analyze the main challenges of technology integration in elementary school social studies education through a systematic literature review approach. This study examines scientific articles published in 2019–2025 from Google Scholar, Scopus, and ScienceDirect using the PRISMA framework. The results of the study show that the main challenges include the limitations of teachers' digital competence, inadequate technological infrastructure, inequality of access to devices and the internet, lack of institutional support, and difficulties in designing interactive and meaningful social studies learning. In addition, the difference in students' digital literacy levels and classroom management constraints also affect the effectiveness of technology-based learning. This study concludes that successful technology integration requires continuous professional development of teachers, infrastructure improvement, and appropriate pedagogical adaptation. The implications of this study emphasize the importance of formulating education policies that focus on equitable access to technology, strengthening digital-based teacher training, and developing innovative social studies learning models that are contextual and student-centered.